Rethinking George MacDonald : Contexts and Contemporaries. - MacLachlan, Christopher (Occasional Papers., 2013)
George MacDonald is the acknowledged forefather of later fantasy writers such as C.S. Lewis and J.R.R. Tolkien. This collection of sixteen essays examines MacDonald's place in the Victorian literary scene, his engagement with his contemporaries and his interest in the social, political, and theological movements of his age.